1991
DOI: 10.1002/mrm.1910220203
|View full text |Cite
|
Sign up to set email alerts
|

Transverse relaxivity of particulate MRI contrast media: From theories to experiments

Abstract: Computer simulations and experimental approach have been used to characterize the properties of particulate MRI contrast agents with special attention paid to the influence of particle size. Up to approximately 50 nm, an increase of the particle diameter leads to a strong enhancement of the transverse magnetization decay rate. For larger grains or aggregates, the decay rate measured without spin-echo formation reaches a plateau. When observed through a spin-echo sequence, the transverse magnetization decay rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
111
1
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(128 citation statements)
references
References 4 publications
14
111
1
2
Order By: Relevance
“…In the presence of stoichiometric quantities of polyvalent biotin-dextran, uncomplexed SA-MACS showed a pronounced increase in hydrodynamic radius and a 2-to 3-fold decrease in T2 relaxivity (data not shown). An inverse relationship between iron oxide cluster size and T2 relaxation rates has been described previously (21) and explained by the extensive theoretical work of Gillis and colleagues (22)(23)(24). For colloidal suspensions of fixed iron oxide volume fraction, the particle size-dependence of T2 relaxivity depends on the quantity ␦ R 2 ͞D, where ␦ is the change in (angular) NMR frequency at the particle equator, R is the radius of the cluster, and D is the self-diffusion coefficient.…”
Section: Mri Signal Changes In Response Tomentioning
confidence: 72%
“…In the presence of stoichiometric quantities of polyvalent biotin-dextran, uncomplexed SA-MACS showed a pronounced increase in hydrodynamic radius and a 2-to 3-fold decrease in T2 relaxivity (data not shown). An inverse relationship between iron oxide cluster size and T2 relaxation rates has been described previously (21) and explained by the extensive theoretical work of Gillis and colleagues (22)(23)(24). For colloidal suspensions of fixed iron oxide volume fraction, the particle size-dependence of T2 relaxivity depends on the quantity ␦ R 2 ͞D, where ␦ is the change in (angular) NMR frequency at the particle equator, R is the radius of the cluster, and D is the self-diffusion coefficient.…”
Section: Mri Signal Changes In Response Tomentioning
confidence: 72%
“…Under this condition, the relaxation rate R 2 * can be ascribed to the dephasing of motionless magnetic moments in a nonuniform field created by randomly distributed magnetic particles. [24][25][26][27][28][29] The value of R 2 * is then given by eq 4: Here, f ) υN is the volume fraction occupied by the particles (υ is the volume of a single particle and N is the number of particles per m 3 ) and R 2 0 is the contribution due to other relaxation mechanisms, such as the diamagnetic relaxation and a contribution as the result of chemical exchange of protons between the surface of the particles and the bulk water protons. Equation 4 was developed for spherical particles.…”
Section: Resultsmentioning
confidence: 99%
“…PROTON T2 RELAXATION MECHANISMS caused by superparamagnetic iron oxide (SPIO) particles are influenced by the strength of magnetic field, particle size, magnetic property of the core, and echo time (1)(2)(3)(4)(5). In addition, it has been reported that the T2 relaxation effect of SPIO strongly depends on its spatial distribution (6 -8).…”
mentioning
confidence: 99%